Analysis of Human Rights, Democracy and Anti-Corruption Values in Islamic Religious Education - Haris Fakhriza; Darul Qutni; Salamah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
Islam is a universal religion that is rahmatan lil alamin. The difference between one individual and another is determined by the quality of his piety, which is a very valid limitation because Islam does not differentiate between humans from certain tribes, races, groups or ethnicities. The aim of this research is analysis of human rights, democracy and anti-corruption values in islamic religious education. This research method uses qualitative research with a literature review type. Data sources use books and research journals. Data collection uses searching for several relevant literature. The data source uses secondary data sources. Data analysis uses content analysis content. The results of this research state that the principles of democracy in Islamic education are imbued with the principles of democracy in Islam, or in other words, democracy in Islamic education is the implementation of the principles of Islamic democracy in Islamic education. The Islamic Religious Education curriculum in schools can support the formation of student character. In cultivating an anti-corruption character, schools need government support as organizers of educational policy. Anti-corruption education needs to be included in the curriculum content as a way for the government to eradicate corruption from an early age.